2010
DOI: 10.1103/physreva.82.033421
|View full text |Cite
|
Sign up to set email alerts
|

State-selective enhanced production of positive ions and excited neutral fragments of gaseous CH2Cl2following Clet al.

Abstract: Following photoexcitation of Cl 2p electrons to various resonances, the dissociation dynamics of ionic and excited neutral fragments of gaseous CH 2 Cl 2 was investigated by combined measurements of photon-induced ionic dissociation, x-ray absorption, and uv-visible dispersed fluorescence. The Cl 2p core-to-Rydberg excitations near the ionization threshold produce a notable enhancement of excited neutral fragments (C * and CH * ), which is attributed to the contribution from a shake-modified resonant Auger dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 52 publications
(73 reference statements)
4
16
0
Order By: Relevance
“…The assignment of the first two absorption bands, designated A and B, is done with the help of ab initio calculations in Figure . Band A is related to the transition Cl (2p 3/2 → 10a 1 * - 200.7 eV), in agreement with previous report, while band B, to the Cl (2p 1/2 → 10a 1 * - 202.8 eV). The first transition to 4b 1 * is around 204 eV (2p 3/2 → 4b 1 *).…”
Section: Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The assignment of the first two absorption bands, designated A and B, is done with the help of ab initio calculations in Figure . Band A is related to the transition Cl (2p 3/2 → 10a 1 * - 200.7 eV), in agreement with previous report, while band B, to the Cl (2p 1/2 → 10a 1 * - 202.8 eV). The first transition to 4b 1 * is around 204 eV (2p 3/2 → 4b 1 *).…”
Section: Results and Discussionsupporting
confidence: 92%
“…The first transition to 4b 1 * is around 204 eV (2p 3/2 → 4b 1 *). The two ionization limits due to the spin–orbit splitting of the 2p hole, Cl 2p 3/2,1/2 → ∞ (IP) are designated by the dotted lines at 206.4 and 208.0 eV, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIY spectra measured for CCl 3 SCN and CCl 2 FSCN near the Cl 2p region are depicted in Figure . The Cl 2p threshold is positioned in the region of 210.0 eV, in accordance with the values previously reported for similar molecules containing chlorinated groups. ,, Centered at about 200.0, 202.0, and 204.0 eV, three wide and not well resolved bands can be observed in this region. Two of these signals could be attributed to electronic transitions related the spin–orbital split of the 2p term in the 2p 1/2 and 2p 3/2 levels of the excited species toward the LUMO+2 (σ* Cl–C ) vacant orbital.…”
Section: Resultssupporting
confidence: 87%
“…They observed that the kinetic energy release of the CH 2 + ion presents a minimum at the Cl (2P 3/2 → 10a 1 *) resonance. Lu et al 8 observed that the CH 2 + ion yield presents a maximum at the Cl (2P 3/2 → 10a 1 *) resonance, which they interpreted as due to a fast dissociation through a highly repulsive potential curve. Alcantara et al 1 presented calculations of the potential curves in order to give support to this assertion.…”
Section: Introductionmentioning
confidence: 99%